Influence of Apis mellifera on the production of blackberry from Castilla (Rubus glaucus Benth.) - BOTERO-GARCES, NATALIA; MORALES-SOTO, GILBERTO (Revista Colombiana de Entomología, 1995)
The pollinating influence of the honey bee,  Apis mellifera L., on the yield of the blackberry (Rubus glaucus Benth.) plants were studied. The experiment was carried out in an Andean blackberry crop in Retiro (Antioquia), (bh-MB). A randomized design of four blocks, 9 replications, and three treatments was used. The treatments were: plants with enclosed florets to exclude pollinators, plants with florets exposed to any pollinating insect, and plants enclosed in insectproof cages with a honey bee nucleus inside to ensure pollination by them. Fruits of each floret were collected, counted, and weighed. An ANOVA showed significative differences between the three treatments (F= 12.13, a = 0.01). Blackberry plants under the influence of A. mellifera yielded significantly more than plants devoid of insect visitors. Plants exposed to the pollinating effect of any insect, including the honey bee, yielded the most. The conclusion is that the Andean blackberry must be pollinated in an adequate way to obtain maximum yield and better quality fruits. The honey bee could be of the utmost usefulness under correct management to achieve this purpose.